Management of Severe Head Injury Patients with Concurrent Metabolic Disorders, Hyperkalemia, Stage III Acute Kidney Injury, and Suspected Alcohol Intoxication Using Renal Replacement Therapy in ICU - Irawati, Dian; Pradian, Erwin (CoinReads Media Prima, 2025)
Introduction: Severe head injury (SHI) presents complex challenges, particularly when complicated by metabolic disorders, hyperkalemia, acute kidney injury (AKI), and suspected alcohol intoxication. These conditions necessitate comprehensive management in the Intensive Care Unit (ICU), often incorporating renal replacement therapy (RRT) to address life-threatening complications. This case highlights the multidisciplinary approach required to optimize outcomes in such critical scenarios. Case Description: A 45-year-old male presented to the ICU with SHI following a motor vehicle accident, exhibiting a Glasgow Coma Scale score of 6. Clinical evaluation revealed hyperkalemia (potassium 6.8 mmol/L), stage III AKI (serum creatinine 4.2 mg/dL), and metabolic acidosis. Suspected alcohol intoxication was noted based on clinical history and odor of alcohol. Initial management included neuroprotective measures, mechanical ventilation, and fluid resuscitation. Continuous renal replacement therapy (CRRT) was initiated to manage hyperkalemia and AKI, stabilizing electrolyte imbalances within 48 hours. Neuroimaging confirmed diffuse axonal injury, prompting anticonvulsant therapy and intracranial pressure monitoring. Multidisciplinary care involving neurology, nephrology, and critical care teams facilitated tailored interventions, resulting in gradual improvement in renal function and consciousness over two weeks. Conclusion: Effective management of SHI with concurrent metabolic disorders, hyperkalemia, AKI, and suspected alcohol intoxication requires integrated ICU care and RRT. Early intervention, precise monitoring, and multidisciplinary coordination are critical for improving patient outcomes in such complex cases.